Efektifitas Pembelajaran Problem Solving Ditinjau dari Daya Juang dan Hasil Belajar Siswa - Dian Mayasari; Sadrack Luden Pagiling (Jurnal Pendidikan Matematika RAFA, 2020)
This study aimed to determine the effectiveness of problem-solving learning reviewed on adversity quotient and student learning outcomes. This research is a quasi-experimental research with the design Nonequivalent Control Group Design. The population in this study were all students of class VII at one of the junior high schools in Merauke, while the random sample was obtained that VII D students became the control class and VII E became the experimental class. The instruments used were tests and non-tests. The data were analyzed in the form of assumption tests with normality and homogeneity tests. With a significance level of 5%, these research results are 1) there are differences in the effectiveness of problem-solving and conventional learning on adversity quotient and student learning outcomes, 2) learning with problem-solving is more effective than conventionally for student learning outcomes, 3) learning with problem-solving is more effective than conventionally against the adversity quotient of students.